PENERAPAN MODEL PEMBELAJARAN TENNIS VERBAL DALAM MENINGKATKAN MOTIVASI BELAJAR PPKn SISWA KELAS VIII SMP NEGERI 21 PEKANBARU - Windari, Windari; Erlinda, Sri; Supentri, Supentri (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: This research was conducted with the aim to determine the effect of tennis verbal learning model in increasing the learning motivation of VIII grade students of SMP Negeri 21 Pekanbaru. This research is motivated by problems found in the learning process which are seen as phenomena that provide awareness for teachers to always provide innovations in the selection and use of models in the learning process. The tennis verbal learning model applies the verbal abilities of students in understanding PKn lessons that are communicated directly by students. The formulation of the problem in this study is "How does the tennis verbal learning model influence the learning motivation of VIII grade students of SMP Negeri 21 Pekanbaru. The purpose of this study was to determine the effect of tennis verbal learning model on learning motivation of eighth grade students of Pekanbaru 21 Junior High School in PKn subjects. The population of this study was all eighth grade students of SMP Negeri 21 Pekanbaru, totaling 386 students and 78 sample students consisting from class VIII 4, VIII 5, and VIII 6. This research was conducted in March-April 2019. The technique of data collection was done by observation, questionnaire, and documentation. The data analysis technique uses descriptive and quantitative analysis methods. The results of this study indicate in the experimental class with an average value for the high category that is 39.75%, the moderate category is 60.25%. While the average value in the control class has an average of 17.95% in the high category, the medium category is 78.20% and the low category is 3.85%. Based on the analysis of the different "t" test the two classes show t count> t table (9.38> 1.66) which means that there is an influence between using the tennis verbal learning model using conventional methods.Key Words: Tennis Verbal, Motivation Study